Modernist Women Writers and War : Trauma and the Female Body in Djuna Barnes, H.D., and Gertrude Stein - Goodspeed-Chadwick, Julie, 1978- (Book collections on Project MUSE., 2011)
In Modernist Women Writers and War, Julie Goodspeed-Chadwick examines important avant-garde writings by three American women authors and shows that during World Wars I and II a new kind of war literature emerged--one in which feminist investigation of war and trauma effectively counters the paradigmatic war experience long narrated by men. In the past, Goodspeed-Chadwick explains, scholars have not considered writings by women as part of war literature. They have limited "war writing" to works by men, such as William Butler Yeats's poem "An Irish Airman Foresees His Death" (1919), which relies